Exploring developmental factors influencing performance excellence in twice-exceptional Saudi athletes: a case study of Paralympic champions - Alarfaj, Abdulhamid A.; Hassan, Marwa M.; Aljohar, Refah M.; Almuaili, Fahad A.; Hassan, Mohamed D. (Frontiers in Psychology, 2025)
IntroductionAchieving exceptional performance in sports, particularly among twice-exceptional athletes, is a multifaceted process that remains underexplored. Understanding the developmental pathways that lead to performance excellence is essential for supporting this unique population.MethodsThis study employed a qualitative case study approach involving three male Paralympic champions (mean age: 33 years). Data were collected using achievement portfolios and in-depth interviews to explore the athletes’ lived experiences and identify influential developmental factors.ResultsTwo distinct developmental stages emerged from the analysis. The first stage, characterized by spontaneous and unstructured motivation, was shaped by psychological and social influences that sparked a general interest in sports. The second stage involved intentional goal setting and structured practice within specialized sports environments. Key factors such as individual growth characteristics and physiological development influenced each stage differently over time.DiscussionThe findings highlight the complex interplay of personal, psychological, social, and contextual factors in the development of performance excellence in twice-exceptional Paralympic athletes. This research contributes to a deeper understanding of how targeted support and recognition of developmental needs can foster sustained athletic excellence.